8q24 risk alleles and prostate cancer in African‐Barbadian men. Issue 16 (22nd September 2014) - Cropp, Cheryl D.; Robbins, Christiane M.; Sheng, Xin; Hennis, Anselm J.M.; Carpten, John D.; Waterman, Lyndon; Worrell, Ronald; Schwantes‐An, Tae‐Hwi; Trent, Jeffrey M.; Haiman, Christopher A.; Leske, M. Cristina; Wu, Suh‐Yuh; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND African American men (AA) exhibit a disproportionate share of prostate cancer (PRCA) incidence, morbidity, and mortality. Several genetic association studies have implicated select 8q24 loci in PRCA risk in AA. The objective of this investigation is to evaluate the association between previously reported 8q24 risk alleles and PRCA in African‐Barbadian (AB) men known to have high rates of PRCA. METHODS Ten previously reported candidate tag SNPs were genotyped and/or imputed in the 8q24 region in 532 AB men with PRCA and 513 AB controls from the Prostate Cancer in a Black Population (PCBP) study. RESULTS Rs2124036 was significant in AB men, (OR = 2.7, 95% CI (1.3–5.3), P = 0.005, Empirical (max (T), corrected for multiple testing) P = 0.03) for the homozygous C/C genotype. Only a single SNP from this region remained statistically significant in our analysis of our AB population. These results may indicate the presence of a founder effect or due to the chosen SNPs not tagging an ancestral haplotype bearing the 8q24 risk allele(s) in this population or could reflect inadequate power to detect an association. We conducted a meta‐analysis including our AB population along with two additional African Caribbean populations from Tobago and Jamaica for SNPs rs16901979 and rs1447295. Meta‐analysis results were most significant for rs16901979 A allele (Z score 2.73; P = 0.006) with a summary OR = 1.31 (95% CI: 1.09–1.58). CONCLUSIONS Additional studies are needed to provide deeper genotype coverage to further interrogate the 8q24 region to understand its contribution to PRCA in this population. Prostate 74: 1579–1588, 2014. © 2014 Wiley Periodicals, Inc.